Analysis of Competitiveness, Opportunities, and Challenges in Indonesia’s Agricultural Trade with the Chinese Market from a Global Perspective - Diana Roofi’u (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study evaluates the competitiveness, opportunities, and challenges of Indonesian agricultural trade within the Chinese market using a descriptive analytical framework. By applying the Revealed Comparative Advantage model and the Export Product Dynamics matrix, this research identifies key commodities with significant export potential and competitive positioning. Results indicate that while Indonesia maintains a strong comparative advantage in primary resource-based exports, the structural dependency on raw material shipments limits overall value-added performance. Furthermore, the analysis highlights that systemic barriers, including stringent international quality standards, technological deficits, and human capital limitations, impede deeper market integration. Addressing these obstacles requires an integrated strategy focusing on industrial downstreaming, enhanced certification compliance, and the digitalization of supply chains. The findings suggest that aligning domestic agricultural policies with regional trade frameworks is essential for fostering sustainable export growth. This research provides a robust academic foundation for policymakers to navigate the complexities of bilateral trade, promoting a transition toward innovation-driven competitiveness that enhances Indonesia's strategic standing in the global agricultural trade architecture.